Pemimpin dari Beberapa Tafsir - Dodi Saputra (Universitas Ahmad Dahlan, 2022)
Being a leader is an easy thing, but being a good leader and being able to carry out the mandate or responsibility is not an easy matter. In Islam itself being a leader or caliph is one of the tasks and goals of humans so that Islam is so careful about matters of leadership. In various verses it is explained related to the concept of leadership, the characteristics of an ideal leader to how to choose a leader in Islam. by using the comparative method, this journal will examine the characteristics of a leader contained in several interpretations interpreted by interpreters. Many in the Qur'an mention the theme of leadership by using various kinds of vocabulary, each word of course has a different meaning and interpretation. Among other things, Hamka's interpretation in Surat al-Maidah verse 57 states that the Koran instructs Muslims not to elect leaders from non-Muslims. Buya Hamka in his commentary on al-Azhar further mentions that there are eight qualifications for leaders, namely: being Muslim, male, intellectual prowess, physical strength, trustworthiness, fairness, honesty and wisdom. As for Tafsir Tanwir from Muhammadiyah which makes Rasulullah and Prophet Ibrahim as examples of ideal leaders who need to be emulated and whose characteristics leaders need to have. According to Ibn Kathir's Interpretation, his interpretation does not merely forbid Muslims from choosing non-Muslims to be leaders, but also forbids even being made close friends, friends and also being appointed as administrators who take care of Muslim matters. According to Jawad Mughniyah in Al-Kasyif's interpretation, for the husband's leadership in the household, to lead his wife, not to become a ruler or dictator.